THE EFFECT OF BALLISTIC EXERCISES USING RUBBER BANDS ON DEVELOPING SPECIAL ENDURANCE AND ACHIEVING 400M PERFORMANCE FOR ATHLETES UNDER 19 YEARS OLD - Nasser, Saadoun (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The speed events are exciting activities that have specific physical requirements to achieve performance and outstanding results and compete internationally. This is particularly important in individual sports, especially for youth categories in athletics. The 400m event is considered one of the most challenging sprint events due to the special physical capabilities required to achieve performance. This race demands a huge amount of speed, endurance, and strength, in addition to the requirements of willpower, determination, and perseverance. Achieving the highest levels in this race necessitates a high level of important fitness components and characteristics. Training for this group of runners focuses on speed endurance and strength endurance through ballistic exercises using rubber bands, which help develop the working muscles of the athletes and enhance their physical capacity, subsequently improving performance. Ballistic exercises with rubber bands are considered modern training methods in athletics, aiming to develop muscular strength through strength training. This type of training forces the athlete's body to recruit and stimulate fast muscle fibers, which is crucial because fast muscle fibers have the potential for growth and development in strength training. The importance of this research lies in using ballistic training with rubber bands to develop special capacities and its impact on performance.